KARAKTER AGRONOMI DAN KADAR BRIX TIGA VARIETAS SORGUM (Sorghum bicolor (L.) Moench) PADA BEBERAPA FASE PERTUMBUHAN - Zilfida, Siti Azira; Anugrahwati, Dwi Ratna; Zubaidi, Akhmad (Agros Journal of Agriculture Science, 2024)
This research aims to determine the agronomic characteristics and Brix levels of three sorghum varieties (Sorghun bicolor (L.) Moench) at several growth phases. The research method uses an experimental method with a factorial completely randomized design (CRD), namely the first factor is variety and the second factor is growth phase. The experiment was carried out in the Glasshouse, Faculty of Agriculture, University of Mataram from May to September 2023. There were 9 treatment combinations, repeated 3 times, so there were 27 experimental units. Observation parameters include plant height, number of leaves, stem diameter, sugar content (brix), dry stover weight and sorghum yield and yield components. Data were analyzed using the Analysis of Variance (ANOVA) Honestly Significant Difference (BNJ) test at a significance level of 5%. The results showed that plant height, sugar content (brix), dry stover weight were significantly different between sorghum varieties, but the number of leaves and stem diameter were not significantly different (non-significant). The parameters of plant height, sugar content (brix), and dry stover weight of the three varieties were significantly different between growth phase treatments, while the number of leaves and stem diameter were not significantly different. All observed parameters were not significantly influenced by the interaction between variety factors and growth phase. Keywords: agronomic characters;brix content; growth phase, sorghum varietiesINTISARIPenelitian ini bertujuan untuk mengetahui karakter agronomi dan kadar brix tiga varietas sorgum (Sorghun bicolor (L.) Moench) pada beberapa fase pertumbuhan. Metode penelitian menggunakan metode eksperimental dengan rancangan acak lengkap (RAL) faktorial, yaitu faktor pertama varietas dan faktor kedua fase pertumbuhan. Percobaan dilaksanakan di Glasshouse Fakultas Pertanian Universitas Mataram dari bulan Mei sampai September 2023. Terdapat 9 kombinasi perlakuan, diulang sebanyak 3 kali, sehingga terdapat 27 unit percobaan. Parameter pengamatan meliputi karakter tinggi tanaman, jumlah daun, diameter batang, kadar gula (brix), bobot brangkasan kering serta hasil dan komponen hasil sorgum. Data dianalisis menggunakan Analysis of Variance (ANOVA) uji Beda Nyata Jujur (BNJ) pada taraf nyata 5%. Hasil penelitian menunjukkan tinggi tanaman, kadar gula (brix), berat brangkasan kering berbeda nyata antar-varietas sorgum, namun jumlah daun dan diameter batang tidak berberbeda nyata (non signifikan). Parameter tinggi tanaman, kadar gula (brix), dan bobot brangkasan kering dari ketiga vrietas berbeda nyata antar-perlakuan fase pertumbuhan, sedangkan jumlah daun dan diameter batang tidak berbeda nyata. Semua parameter pengamatan tidak dipengaruhi secara nyata oleh interaksi antara faktor varietas dan fase pertumbuhan.Kata kunci: fase pertumbuhan; kadar brix; karakter agronomi; sorgum